الاجتهاد عند الشيخ الرئيس أبي نبهان جاعد بن خميس الخروصي : دراسة تحليلية - خروصي، أحمد سالم موسى
This analytical study aims to demonstrate the two important aspects of Al-Ijtihad according to al-Shaykh al-Ra´is Abu Nabhan Ja´id bin Khamis Al-Kharusi. The first aspect is related to the personality of Abu Nabhan and its features in terms of his auspicious upbringing, personal life and political movement while he was living during the Al-Busaidi state. Additionally, how did the aforementioned aspects shape his personality to engage in the crucial events witnessed by the Omani community and the surrounding region at that time? Besides that, the study illustrates the various positions that Abu Nabhan occupied scientifically and politically during the journey of ninety years of his life according to available sources, viz, manuscripts and printed studies. The second aspect of this research focuses on the principle thoughts and opinions of Abu Nabhan by analysing his methods and tools of studying the fundamental and fringe Islamic evidences as well as the rules of Islamic laws. Moreover, the research sheds light on his remarkable attention to vital issues of public and private life. The conclusion of this study elaborates the details of his own style of explaining the aspects of jurisprudence and the principles of the jurisprudence. The methodology of this study was based on three approaches: inductive by collecting data from its various sources, both manuscripts and published books and the second is historical by studying the historical stages and conditions of that era. The final approach is by analysing the ideas and opinions of Abu Nabhan in the jurisprudence and its principles. Findings of this study have shown that Abu Nabhan had devoted and dedicated his whole life gaining knowledge. Then he carried out the mission of imparting sound thoughts and ideas among the public and tries to find solutions to the problems and challenges being occurred by internal or external causes such as the invasion the Wahhabism to Oman and the consequences of Western Colonisation. It is evident that the most of his efforts were to encounter the challenges and obstacles in the Omani lands. Finally, while Abu Nabhan had striven significantly to find solutions for the political and social issues and matters, he had simultaneously contributed immensely in the scholarly field by analysing and correcting various ideas and thoughts. Until to this very day, the scholarly heritage of Abu Nabhan has been used to deal with complicated matters and contemporarily cases including theological issues and Islamic legal opinions.